Peran Ilmu Ma’ani dalam Menyampaikan Pesan Moral dalam Al–Qur’an - Sofi`, Utari Nur; Azizah, Shinta Afifatul; Mubarak, Imad Zakky (Maliki Interdisciplinary Journal, 2025)
This article examines the role of ma’ani in conveying moral messages in the Qur’an. Ma’ani, which refers to the meanings or content within the text, plays a crucial role in understanding the moral messages delivered by Islam's holy scripture. This study focuses on how language structure, contextual usage, and interpretative approaches to ma’ani uncover profound ethical and moral values. In the Qur’an, moral messages are conveyed through various linguistic styles, including metaphors, analogies, and the stories of prophets. The article elaborates on how interpretations of ma’ani help readers comprehend these moral messages more clearly, enabling the application of values such as justice, compassion, and social responsibility in daily life. This research employs textual analysis with a thematic exegesis approach to explore the relationship between ma'any and moral messages. The findings reveal that understanding ma'any requires not only linguistic knowledge but also an awareness of the historical and social contexts during the Qur’an's revelation. Thus, this article emphasizes the importance of studying ma'any to comprehend the Qur’an as a timeless guide to morality.